Transient processes in Q-cascades for separation of multicomponent mixtures. (4th May 2015) - Smirnov, A.Yu.; Sulaberidze, G.A.; Borisevich, V.D.; Zeng, S.; Jiang, D.
Abstract: The model of transient multicomponent mass transfer in a Q -cascade is developed. It enables to study the physical regularities of alteration of concentrations along the cascade stages and in the product flow from the cascade. The capability of the developed model is demonstrated by calculation of the transient process and the time-to-steady-state in a gas centrifuge cascade for separation of krypton isotopes. Highlights: The model of the transient multicomponent mass transfer in a Q -cascade is developed. The obtained analytical solution qualitatively coincides with the numerical one. The regularities of the transient multicomponent mass transfer are studied. The minimum time to reach the steady-state of a separation cascade is assessed.